Uma abordagem para a classificação de imagens histológicas para o auxílio da detecção do câncer colorretal baseado em transfer learning - Ohata, Elene Firmeza (2021)
Colorectal cancer (CRC) is the second most diagnosed cancer in the United States. It is identified by histological evaluations of microscopic images of the cancerous region, relying on a subjective interpretation. The Colorectal Cancer Histology dataset used in this study contains 5000 images, made available by the University Medical Center Mannheim. This approach proposes the automatic identification of eight types of tissues found in CRC histopathological evaluation. We apply Transfer Learning from architectures of Convolutional Neural Networks (CNNs). We modified the structures of CNNs to extract features from the images and input them to well- known machine learning methods: Naive Bayes, Multilayer Perceptron, k-Nearest Neighbors, Random Forest, and Support Vector Machine (SVM). We evaluated 108 extractor-classifier combinations. The one that achieved the best results is DenseNet169 with SVM (RBF), reaching an Accuracy of 92.083% and F1-Score of 92.117%. Therefore, our approach is capable of distinguishing tissues found in CRC histological evaluation.